Ready player one - Cline, Ernest (New York : B D W Y Broadway Books, 2017)
It's the year 2044, and the real world is an ugly place. Like most of humanity, Wade Watts escapes his grim surroundings by spending his waking hours jacked into the OASIS, a sprawling virtual utopia that lets you be anything you want to be; a place where you can live and play and fall in love on any of ten thousand planets. And like most of humanity, Wade dreams of being the one to discover the ultimate lottery ticket that lies concealed within this virtual world. For somewhere inside this giant networked playground, OASIS creator James Halliday has hidden a series of fiendish puzzles that will yield massive fortune--and remarkable power--to whomever can unlock them.
Includes an excerpt from Armada.
Keywords: Regression (Civilization) -- Fiction; Virtual reality -- Fiction; Shared virtual environments -- Fiction; Utopias -- Fiction; Puzzles -- Fiction; Science fiction